2021
DOI: 10.31487/j.scr.2021.04.05
|View full text |Cite
|
Sign up to set email alerts
|

Complete Thoracic Ectopia Cordis, Dilemma of the Outcome: A Case Report

Abstract: Background: Ectopia Cordis (EC) is a rare congenital condition where the heart is partially or completely lies outside the thoracic cavity (extrathoracic), uncovered by pericardium and skin. Many works of literature reported EC is a rare congenital abnormality with an incidence of about 5-8 per 1 million live births and includes about 0.1% of congenital heart diseases. Methods: This was a male baby, weighing 2.900 kg, received with cyanosis with a defect in the anterior chest wall and heart protruding out thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…They concluded that the degree and level of exposure of the heart preclude initial survival, and complex repairs of intracardiac defects may be difficult in cases requiring shunts for long-term palliation [ 26 ]. In the same year in Iraq, Aboud et al reported a case of complete thoracic ectopia cordis, but due to poor general condition, the newborn expired on 36 hours of life before any intervention [ 27 ]. Another case of thoracoabdominal ectopia cordis from Tanzania was reported by Lodhia et al but in view of the lack of a cardiac center and waiting for relocating the patient to a cardiac institute, the newborn had a cardiac arrest on the fifth day of life and surgery of relocating the heart was not carried out [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the degree and level of exposure of the heart preclude initial survival, and complex repairs of intracardiac defects may be difficult in cases requiring shunts for long-term palliation [ 26 ]. In the same year in Iraq, Aboud et al reported a case of complete thoracic ectopia cordis, but due to poor general condition, the newborn expired on 36 hours of life before any intervention [ 27 ]. Another case of thoracoabdominal ectopia cordis from Tanzania was reported by Lodhia et al but in view of the lack of a cardiac center and waiting for relocating the patient to a cardiac institute, the newborn had a cardiac arrest on the fifth day of life and surgery of relocating the heart was not carried out [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic foot ulcers (DFUs), a major complication of diabetes, are hard-to-heal wounds that affect millions of people (2.49 million) in the U.S., with yearly incidence ranging from 2% to 6% and an average annual Medicare expenditure of $29.16 billion. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] DFUs usually suffer from a long healing cycle (78 days on average) and a high recurrence rate (40% of DFU patients have a recurrence within one year of ulcer healing). Adequate offloading, which alleviates pressure from the ulcer site, is critical for aiding in ulcer treatment.…”
Section: Introductionmentioning
confidence: 99%